Peningkatan Literasi Digital untuk Administrasi Desa Mareje dalam Mendukung Transformasi Digital Pelayanan Publik - Muhammad Imam Dinata; Siti Agrippina Alodia Yusuf; Idham; Hady Rasikhun (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
Digital literacy among village officials and the continued dominance of manual administrative processes remain obstacles to the implementation of digital-based administrative systems. This community service activity aims to enhance the digital literacy of village officials and the community of Mareje Village in supporting the digital transformation of public services. The activity was conducted in Mareje Village, Lembar District, West Lombok Regency, West Nusa Tenggara Province, in February 2026 using a participatory approach through stages of observation, socialization, training, mentoring, and evaluation. The training materials included an introduction to village administration applications, hardware requirements, application installation, and direct practice in using village administration applications. The results of the activity showed an improvement in participants’ understanding and skills in utilizing information technology for village administration. The implementation of digital administrative applications was able to accelerate service processes, simplify document archiving, improve work efficiency, and support transparency in public services. In addition, participants demonstrated a more positive attitude toward the use of digital technology in village administration. Nevertheless, infrastructure limitations, such as the limited number of computer devices and unstable internet access, remain challenges in implementing village digital transformation. Therefore, this activity serves as a strategic step in supporting a more modern, effective, and integrated village governance system based on information technology.